2012
DOI: 10.1080/13607863.2011.651438
|View full text |Cite
|
Sign up to set email alerts
|

Experience of aging in patients with rheumatic disease: A comparison with the general population

Abstract: Objectives: Self-perceptions of aging have been shown to predict mental and physical health and even longevity. This study examined the aging perceptions of patients with rheumatic disease and compared them with the general Dutch population. Methods: Consecutive patients visiting a rheumatology clinic completed the Personal Experience of Aging Scale (PEAS) subscales: physical decline, social loss, continuous growth, and two sentence stems from the SELE instrument (What I like/do not like about getting older . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…Our results did not replicate the low reliability of the subscale which was found in a previous study with arthritis patients (Bode et al, 2012). Cronbach’s alpha in the current study came close to the level of internal consistency found in the two national surveys (Steverink et al, 2001; Westerhof, 2003) and was in accordance with the proposed criterion for good internal consistency (Nunnally & Bernstein, 1994; Terwee et al, 2007).…”
Section: Discussion (Cirf Category 8)contrasting
confidence: 99%
See 1 more Smart Citation
“…Our results did not replicate the low reliability of the subscale which was found in a previous study with arthritis patients (Bode et al, 2012). Cronbach’s alpha in the current study came close to the level of internal consistency found in the two national surveys (Steverink et al, 2001; Westerhof, 2003) and was in accordance with the proposed criterion for good internal consistency (Nunnally & Bernstein, 1994; Terwee et al, 2007).…”
Section: Discussion (Cirf Category 8)contrasting
confidence: 99%
“…In a prior study with arthritis patients, we used the Personal Experience of Aging Scale (PEAS; Bode, Taal, Westerhof, van Gessel, & van de Laar, 2012; Steverink, Westerhof, Bode, & Dittmann-Kohli, 2001) and compared the outcomes with those in the general population. It was found that the Physical Decline (PD) subscale produced a low internal consistency in the patient sample, relative to the general population samples.…”
Section: The Personal Experience Of Aging Scalementioning
confidence: 99%
“…Conversely, older adults with family dysfunctions have a more negative self‐perception of ageing. The family is the most basic social unit; it is related closely to the life and health of elderly people and provides their main spiritual and psychological support (Bode et al., 2012 ). If older people receive appropriate care and support from their families, they will be able to negotiate the ageing process successfully and maintain their physical and mental health by developing a positive self‐perception of ageing.…”
Section: Discussionmentioning
confidence: 99%
“…From the old person's point of view, the decreased functional ability and suffering from various health complaints also means dependency on family members as well as others for carrying out daily activities (Andersson et al, 2008). These perceptions are, multidirectional and multidimensional, implying that individuals experience both gains and losses in different domains, such as physical, psychological, and social functioning (Bode et al, 2012). It is difficult for older one to leave the position where they get respect, regular income and social network of friends, colleagues and acquaintances; similarly, it causes transition from the daily recognition to one with limited recognition and possible isolation and it creates psychological problems of elderly people (Ghimire & Gurung, 2014).…”
Section: Social Sciencementioning
confidence: 99%